A Study of Onychoscopic Findings in Various Dermatological Disorders - Snehal Shivaji Shelke; Varsha P Jamale; Asma Arif Hussain; Mohan S Kale; Balkrishna P Nikam; Mansi Milind Bhatt (Wolters Kluwer Medknow Publications, 2024)
Context: About 10% of all the dermatological conditions are comprised nail disorders. It is challenging for the dermatologists to diagnose nail disorders quickly without the help of invasive procedures. Aims: The aim of the study was to evaluate onychoscopic patterns associated with various nail disorders. Settings and Designs: Hospital-based cross-sectional observational study was conducted at a tertiary care teaching institute in Maharashtra, India from November 2019 to May 2021. Materials and Methods: One hundred and fifty patients, with a history and clinical presentation suggestive of nail disorders, were recruited in the study after confirming the clinical diagnosis. Patients having secondarily modified lesions were excluded. Dry as well as wet onychoscopy using polarized and nonpolarized modes was performed with the help of DermLite 4 dermoscope with an attached OnePlus 8T mobile phone camera to capture and save the dermoscopic images. Data were compiled and statistically analyzed using SPSS version 21.0. Statistical Analysis Used: Categorical variables were expressed in frequency and percentages. Data were entered in Microsoft Excel and analyzed using SPSS version 20. P value (using Z-test for proportions) was calculated wherever needed. Results: The majority of the patients were in the age group of 21-50 years with slight male preponderance. Overall most common onychoscopic findings studied in all the disorders were the nail plate alterations followed by chromonychia. The most common nail changes associated with connective tissue disorders were changes in the proximal nail fold capillaries along with changes in the curvature. The most common change observed in onychomycosis was chromonychia. Aurora borealis, spikes, and jagged edges of onycholytic plate with ruin pattern of hyperkeratosis were specific to onychomycosis. Inflammatory disorders of the nail unit (e.g., lichen planus and nail psoriasis) showed nail plate alterations with increased nail plate fragility. Conclusions: Some onychoscopic patterns are observed consistently with certain diseases, and these can be used for their diagnosis, hence, avoiding unnecessary biopsies, thus improving the patient outcome.